Futures Literacy Zukunftsgestaltungskompetenzen für die berufliche Lehrkräftebildung - Banek, Natalie; Steuber, Ariane; Gillen, Julia (Beiträge zur Pädagogik, 2023)
What competences do teachers and training staff in vocational education and training need in order to be able to professionally master pedagogical challenges in complex and dynamic teaching-learning situations? The Leibniz works 4.0 project, funded by the BMBF, is particularly dedicated to such questions, which result from changed learning and working environments in vocational teacher training. Based on UNESCO's concept of Futures Literacy, the volume looks at cross-sectional educational tasks such as digitalisation and inclusion from interdisciplinary perspectives in order to open up theoretical approaches for vocational education and training and to provide suggestions for pedagogical practice in vocational education and training contexts. With contributions by Johanna Backhaus | Natalie Banek | Julia Gillen | Sandra Heiligmann | Tobias Key | Manuel King | Janine Michele | Stefan Nagel | Shana Rühling | Johannes Schäfers | Sylvia Schweigler | Ariane Steuber | Sabine Struckmeier | Jana Wende | Fritz Wilhelms